Medical innovation in the Amazon: the first University Headache Clinic - Magalhães, Átila Barros; Amorim, Samuel Oliveira de; Ferreira, Matheus da Silva; Maia, Matheus da Silveira; Coelho, Thyerre Castro; Camarão, Ana Karoline Pereira; Honorato, Marcos Manoel (Headache Medicine, 2024)
IntroductionHeadache is one of the main neurological complaints worldwide. In Brazil, the lack of specialized centers, especially in less developed regions, hinders adequate treatment, impacting the health and quality of life of these populations. ObjectiveTo report the implementation of the first university headache clinic in the Brazilian Amazon. MethodsThis experience report aims to identify, record, and analyze characteristics, factors, or variables related to the implementation of a headache clinic in the Brazilian Amazon. ResultsThe Amazon Headache Clinic, a pioneer in the region, served 70 patients between May 2023 and February 2024. Fifty-eight patients are under continuous follow-up, while 36 are awaiting their first appointment. Preliminary data show a higher presence of females, with an average age of 37.96 years, predominantly students, and a diagnosis of episodic migraine without aura. Both in-person and telemedicine consultations prioritize financially disadvantaged patients, promoting accessibility to specialized headache treatment. The service, provided in-person in the city of Santarém and via telemedicine to riverside communities, represents a significant advancement in headache management in the region, significantly improving patients' quality of life. Medical students and residents accompany specialists, contributing to their practical healthcare training. ConclusionThe inauguration of the first headache clinic in the Amazon marks an important milestone in regional healthcare and medical research. In addition to filling a gap in the treatment of these conditions, it promotes the training of local professionals, improves patients' quality of life, and drives advances in healthcare.